EFEITO RESIDUAL DA ADUBAÇÃO FOSFATADA NO SOLO SOBRE A CULTURA DO MILHO - Bellingieri, P. A.; Moares, J. F. L.; Zanin, E. S.; Freitas, J. C. (REVISTA DE AGRICULTURA, 2015)
EFEITO RESIDUAL DA ADUBAÇÃO FOSFATADA NO SOLO SOBRE A CULTURA DO MILHO